Responder
To express each exponential function in the form \( 3^{k x} \), find the suitable constant \( k \) for each:
1. **First Set:**
- \( 4^{x} = 3^{\log_3 4 \cdot x} \) → \( k = \log_3 4 \)
- \( (\sqrt{3})^{x} = 3^{\frac{1}{2} x} \) → \( k = \frac{1}{2} \)
- \( \left(\frac{1}{9}\right)^{x} = 3^{-2x} \) → \( k = -2 \)
2. **Third Set:**
- \( 8^{\frac{2x}{3}} = 3^{2 \log_3 2 \cdot x} \) → \( k = 2 \log_3 2 \)
- \( 9^{\frac{3x}{2}} = 3^{3x} \) → \( k = 3 \)
- \( 16^{-\frac{3x}{4}} = 3^{-3 \log_3 2 \cdot x} \) → \( k = -3 \log_3 2 \)
3. **Fifth Set:**
- \( \left(\frac{1}{4}\right)^{2x} = 3^{-2 \log_3 4 \cdot x} \) → \( k = -2 \log_3 4 \)
- \( \left(\frac{1}{8}\right)^{-3x} = 3^{3 \log_3 8 \cdot x} \) → \( k = 3 \log_3 8 \)
- \( \left(\frac{1}{81}\right)^{\frac{x}{2}} = 3^{-2x} \) → \( k = -2 \)
**Summary:**
- For each exponential function, express it in the form \( 3^{k x} \) by finding the appropriate constant \( k \) based on the base of the original function.
Solución
It looks like you want to express each of the given exponential functions in the form \( 3^{k x} \) by finding the suitable constant \( k \). Let's analyze each expression one by one.
### 1. \( 4^{x}, \ (\sqrt{3})^{x}, \ \left(\frac{1}{9}\right)^{x} \)
#### a. \( 4^{x} \)
First, express 4 as a power of 3:
\[
4 = 3^{\log_3 4}
\]
So,
\[
4^{x} = \left(3^{\log_3 4}\right)^{x} = 3^{x \cdot \log_3 4}
\]
**Thus, \( k = \log_3 4 \).**
#### b. \( (\sqrt{3})^{x} \)
\[
\sqrt{3} = 3^{1/2}
\]
So,
\[
(\sqrt{3})^{x} = \left(3^{1/2}\right)^{x} = 3^{(1/2) x}
\]
**Thus, \( k = \frac{1}{2} \).**
#### c. \( \left(\frac{1}{9}\right)^{x} \)
\[
\frac{1}{9} = 9^{-1} = (3^{2})^{-1} = 3^{-2}
\]
So,
\[
\left(\frac{1}{9}\right)^{x} = \left(3^{-2}\right)^{x} = 3^{-2x}
\]
**Thus, \( k = -2 \).**
### 3. \( 8^{\frac{2x}{3}}, \ 9^{\frac{3x}{2}}, \ 16^{-\frac{3x}{4}} \)
#### a. \( 8^{\frac{2x}{3}} \)
\[
8 = 2^{3} = \left(3^{\log_3 2}\right)^{3} = 3^{3 \log_3 2}
\]
So,
\[
8^{\frac{2x}{3}} = \left(3^{3 \log_3 2}\right)^{\frac{2x}{3}} = 3^{2x \cdot \log_3 2}
\]
**Thus, \( k = 2 \log_3 2 \).**
#### b. \( 9^{\frac{3x}{2}} \)
\[
9 = 3^{2}
\]
So,
\[
9^{\frac{3x}{2}} = \left(3^{2}\right)^{\frac{3x}{2}} = 3^{3x}
\]
**Thus, \( k = 3 \).**
#### c. \( 16^{-\frac{3x}{4}} \)
\[
16 = 2^{4} = \left(3^{\log_3 2}\right)^{4} = 3^{4 \log_3 2}
\]
So,
\[
16^{-\frac{3x}{4}} = \left(3^{4 \log_3 2}\right)^{-\frac{3x}{4}} = 3^{-3x \cdot \log_3 2}
\]
**Thus, \( k = -3 \log_3 2 \).**
### 5. \( \left(\frac{1}{4}\right)^{2x}, \ \left(\frac{1}{8}\right)^{-3x}, \ \left(\frac{1}{81}\right)^{\frac{x}{2}} \)
#### a. \( \left(\frac{1}{4}\right)^{2x} \)
\[
\frac{1}{4} = 4^{-1} = \left(3^{\log_3 4}\right)^{-1} = 3^{-\log_3 4}
\]
So,
\[
\left(\frac{1}{4}\right)^{2x} = \left(3^{-\log_3 4}\right)^{2x} = 3^{-2x \cdot \log_3 4}
\]
**Thus, \( k = -2 \log_3 4 \).**
#### b. \( \left(\frac{1}{8}\right)^{-3x} \)
\[
\frac{1}{8} = 8^{-1} = \left(3^{\log_3 8}\right)^{-1} = 3^{-\log_3 8}
\]
So,
\[
\left(\frac{1}{8}\right)^{-3x} = \left(3^{-\log_3 8}\right)^{-3x} = 3^{3x \cdot \log_3 8}
\]
**Thus, \( k = 3 \log_3 8 \).**
#### c. \( \left(\frac{1}{81}\right)^{\frac{x}{2}} \)
\[
\frac{1}{81} = 81^{-1} = \left(3^{4}\right)^{-1} = 3^{-4}
\]
So,
\[
\left(\frac{1}{81}\right)^{\frac{x}{2}} = \left(3^{-4}\right)^{\frac{x}{2}} = 3^{-2x}
\]
**Thus, \( k = -2 \).**
---
### Summary of Constants \( k \)
1. **First Set:**
- \( 4^{x} = 3^{(\log_3 4) x} \) → \( k = \log_3 4 \)
- \( (\sqrt{3})^{x} = 3^{\frac{1}{2} x} \) → \( k = \frac{1}{2} \)
- \( \left(\frac{1}{9}\right)^{x} = 3^{-2x} \) → \( k = -2 \)
3. **Third Set:**
- \( 8^{\frac{2x}{3}} = 3^{2 (\log_3 2) x} \) → \( k = 2 \log_3 2 \)
- \( 9^{\frac{3x}{2}} = 3^{3x} \) → \( k = 3 \)
- \( 16^{-\frac{3x}{4}} = 3^{-3 (\log_3 2) x} \) → \( k = -3 \log_3 2 \)
5. **Fifth Set:**
- \( \left(\frac{1}{4}\right)^{2x} = 3^{-2 (\log_3 4) x} \) → \( k = -2 \log_3 4 \)
- \( \left(\frac{1}{8}\right)^{-3x} = 3^{3 (\log_3 8) x} \) → \( k = 3 \log_3 8 \)
- \( \left(\frac{1}{81}\right)^{\frac{x}{2}} = 3^{-2x} \) → \( k = -2 \)
---
**Note:** \( \log_3 a \) represents the logarithm of \( a \) with base 3. Depending on the context or the specific requirements of your problem, you might need to simplify these logarithmic expressions further or leave them as is.
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución